December 7th the fleet that came to stay. (New York Good Times Home Video, 2001)
Brigadier General Stanley M. Ulanoff, a widely decorated military historian who served with the Counterintelligence Corps in Europe during World War II, introduces this gripping documentary film. At 7:55 am on sunday, December 7th, 1941, which FDR called "a date which will live in infamy", the Japanese began an air attack that devastated the Pacific fleet and took the lives of 2,343 servivemen. Lt.Cmdr. John Ford skillfully blends historic action with studio shots in this OSCAR®-winning look at the day's events.
December 7th -- Messengers of Death -- Battle stations -- The second phase -- All Americans -- The Facts -- The fleet that came to stay -- Rattling the lock -- Farewell.
Dolby digital.
In English.
Keywords: World War, 1939-1945 -- Motion pictures and war; Pearl Harbor (Hawaii) -- Attack on, 1941.